Espaço de Moçambique nas relações Brasil-África: breve análise da política externa brasileiro para a África: BRIEF ANALYSIS OF THE BRAZILIAN EXTERNAL POLICY FOR AFRICA - Cuco, Arcenio Francisco (2019)
Although Brazil-Africa relations are marked by advances and setbacks, undoubtedly, in the context of the foreign policy developed by the Lula government (without taking advantage of its predecessors), they have played a prominent role. During the Lula administration, the effort to get closer to Africa gained momentum, not only because of the renewed role of the African continent in international politics, as the last frontier of economic internationalization, but also through the adoption of a foreign policy line that favors multiraterism, with The objective of this article is to analyze the impact of the Brazilian Foreign Policy (PEB) in Africa, seeking to understand the space that Mozambique occupies within this policy. The question that guides the ideas exposed in the text is the following one: How is Mozambique inserted in the plan of the Brazilian Foreign Policy for Africa? The bibliographic review and the analysis of some documents were the main way of searching for information that support the ideas presented in the article.